Cost-effectiveness of sacituzumab tirumotecan in previously treated metastatic triple-negative breast cancer in China - Shuo Kang; Shuo Yang; Yize Jia; Shan Zhao (PLoS ONE, 2026)
Background The OptiTROP-Breast01 trial demonstrated the efficacy of sacituzumab tirumotecan for patients with metastatic triple-negative breast cancer (TNBC). The current analysis evaluated the cost-effectiveness of sacituzumab tirumotecan compared with chemotherapy for patients with metastatic TNBC from the Chinese health-care system perspective. Methods A partitioned survival model (PSM) was developed to simulate 3-week patients in 10-year time horizon to access the disease course and cost-effectiveness of sacituzumab tirumotecan compared with chemotherapy for metastatic TNBC patients, cost and utility values were gathered from the dataset and published studies, annual discount rate of 5% was used. Total cost, life-years (LYs), quality-adjusted life-years (QALYs), and incremental cost-effectiveness ratio (ICER) were the model outputs. Sensitivity analyses and subgroup analyses were conducted to estimate the robustness of the model outcomes. Results In base-case analysis, compared with chemotherapy, sacituzumab tirumotecan could bring additional 0.41 LYs and 0.35 QALYs, with marginal costs of $55,927.31, resulting in the ICER of $162,799.04/QALY, which high than the willingness-to-pay (WTP) threshold of $40,326 per additional QALY gained. One-way sensitivity analyses revealed that the utility value was the main driver of the model outputs. Probabilistic sensitivity analyses showed the cost-effective probability of sacituzumab tirumotecan was 0% at the WTP threshold of $40,326/QALY. Subgroup analyses suggested that sacituzumab tirumotecan could not be considered cost-effective for all subgroup patients. Conclusion Sacituzumab tirumotecan was unlikely to be the cost-effective option for patients with metastatic TNBC compared with chemotherapy from the Chinese health-care system perspective, reduced the price of sacituzumab tirumotecan could increase its cost-effective.